Risk, returns, and biases of listed private equity portfolios - Stéphanie Bilo; Hans Christophers; Michèl Degosciu; Heinz Zimmermann (University of Basel, Center of Business and Economics (WWZ), 2005)
This is the first empirical paper investigating a comprehensive sample of listed (i.e. publicly traded) private equity companies, covering 287 companies in the time period 1986 to 2003. After imposing liquidity constraints, and after correcting for non-surviving vehicles, we get a sample of 114 instruments. The risk and return characteristics of three portfolio strategies, two partially rebalanced and one fully rebalanced, are compared. We moreover address potential biases resulting from thin trading, the bid-ask spread, and sample selection. We show that the adjusted performance figures differ substantially from standard estimates. But even after correcting for these biases, we find a high risk-adjusted performance of this asset class before 2000, and dramatic different results between the three indices if we extend the time period to 2003.Listed private equity, Private equity, Performance biases
Keywords: G24; 330; Listed private equity; Private equity; Performance biases